Pengaruh Human Capital, Structural Capital, Relational Capital, Dan Digital Marketing Terhadap Kinerja Umkm (Studi Pada Umkm Makanan Dan Minuman Binaan Program Satrya Emas Kabupaten Pasuruan - rahmadian, Rahmadian Nadiatus Shaniar Puteri; Nuraeni (CV. Satria Jaya, 2024)
This study aims to determine the effect of human capital, structural capital, relational capital, dan digital marketing on the performance of SME. The research method used is uantitative with multiple linier regression analysis. Population in tjis study SME food and drink under the guidance of the satrya emas program in Pasuruan Regency. The sample in this study was 138 SME. Using method random sampling. And the result of study show human capital, structural capital, relational capital, dan digital marketing has an effect on the performance of the SME